Corroboration of RIPng, EIGRPv6 and OSPFv3 Routing Protocols in IPv6 Environment through Simulation and Actual Operation - J. Sebial, Archival; ., . (International Journal of Engineering and Technology, 2018)
The IPv4 address exhaustion is incipient and apparent with the growing computer network system technologies. The computing world is moving to the adoption of the next generation Internet Protocol, IPv6. Such transition poses immense and significant considerations; specifically, in building networks and in the identification of suitable routing protocols for computer integration with high degree of adaptability. As routing plays a significant and major component in network’s performance, performance reference evaluation of RIPng, EIGRPv6 and OSPFv3 in IPv6 setting is undertaken and studied. This paper focused on testing the performance consistency of the RIPng, EIGRPv6 and OSPFv3 routing protocols in simulation and actual operations in IPv6 environment. A packet tracer was used during simulation and corroborated to real time situation. Performances in both simulation and actual operation yielded similar results, with high consideration on setting parameters consistently. The mock-up process had been authenticated by the actual set-up. It is therefore recommended that simulation should be considered in studying the behavior of the system before building it as results are reliable in general.. Integration of simulation for networking configurations is not only cost-effective but also creativity and learning-supportive.  Moreover, network administrators can engage into network services through abstraction of higher-level functionality that is changing, economic and adjustable which is ideal for the dynamic nature of today’s applications.